Association of Vitamin-D-Related Genetic Variations and Treatment Response to Pegylated Interferon in Patients with Chronic Hepatitis B. Issue 8 (November 2017) - Limothai, Umaporn; Chuaypen, Natthaya; Khlaiphuengsin, Apichaya; Chittmittraprap, Salyavit; Poovorawan, Yong; Tangkijvanich, Pisit
Background: Vitamin D, a potent immune-modulator, has been linked to the pathogenesis of chronic hepatitis B (CHB). This study was aimed at investigating the association between single nucleotide polymorphisms (SNPs) in vitamin-D-related genes and treatment response to pegylated interferon (PEG-IFN) in patients with CHB. Methods: A total of 275 Thai patients (122 hepatitis B e antigen [HBeAg]-positive and 153 HBeAg-negative CHB) treated with 48-week PEG-IFN were recruited. Virological response (VR) at 48 weeks post-treatment was defined as HBeAg seroconversion plus HBV DNA <2, 000 IU/ml for HBeAg-positive CHB and HBV DNA <2, 000 IU/ml for HBeAg-negative CHB. The SNPs VDR (rs2228570), DBP (rs7041) and CYP27B1 (rs4646536) were analysed. Results: The distribution of TT, CT and CC genotypes of rs4646536 in this cohort was 21.8%, 46.2% and 32.0%, respectively. There was no difference in its distribution according to HBeAg status. In HBeAg-positive CHB, patients with TT genotype, compared with non-TT genotype, achieved higher VR (53.3% versus 31.5%; P =0.032) and hepatitis B surface antigen (HBsAg) clearance (20.0% versus 5.4%; P =0.016). In HBeAg-negative CHB, the corresponding figures were 60.0% versus 30.9% ( P =0.003) and 16.7% versus 5.7% ( P =0.045), respectively. Patients with TT genotype had more rapid HBsAg decline than those with non-TT genotype. However, SNPs rs2228570 and rs7041were not associated with VR and HBsAg clearance. Logistic regression analysis demonstrated that SNP rs4646536 and baseline HBsAg level were independent predictors of VR in both HBeAg-positive and HBeAg-neg-ative CHB. Conclusions: Our data suggest that SNP rs4646536 in the CYP27B1 gene is a predictive factor of response to PEG-IFN therapy in Thai patients with CHB.